Modelling Academic Performance in Science-Based Subjects in Primary Schools Using Elements of Teacher Preparation in Uganda - Wafula, Alfred; Oriangi, George; Odama, Stephene; Ofoyuru, Denis Thadeus; Ogwang, Tom Henry; Ologe, Daniel Ochieng (East African Journal of Education Studies, 2023)
ow academic performance in science subjects has continued to characterise primary education in sub–Saharan Africa, despite several interventions by stakeholders. This study investigated the influence of teachers’ preparation for teaching and learning on pupils’ academic performance in mathematics and integrated science in Kigumba town council in Uganda. It used a cross-sectional survey design with a sample size of 180 teachers and pupils from both government-aided and privately funded schools. Interviews were used to collect data. Descriptive statistics was used to determine teachers’ level of preparation for teaching and learners’ level of academic performance, while a regression model was used to establish the influence of teacher’s preparation on pupils’ academic performance. Findings indicate that teachers’ level of preparation was generally good and significantly (P<0.05) influenced by their teaching experience and access to insurance. Furthermore, academic performance in mathematics and integrated science was significantly influenced by teacher preparation (P<0.05) arising from lesson planning, updating learners’ discipline records, and creativity. In conclusion, teachers need to continue being creative, planning lessons on a daily basis, and updating learners’ discipline records in order to improve pupil performance. In turn, the government needs to provide teachers with insurance coverage, e.g., health insurance, in order to free more of their time for lesson preparation. The study informs education and economic planning policies